Perancangan Interior Arts Center dengan Pendekatan Ruang Fleksibel - Devina Ancilla; Sriti Mayang Sari; Jean Francois Poilot (Intra, 2016)
Surabaya as the capital of East Java province has a lot of communities who interest in arts. Art developments in Surabaya itself never diminished, it can be seen by many artists and art communities that exist, both in East Java and Surabaya. But there are still lack an adequate place to facilitate the arts in Surabaya, causing many artists lost his job for not having a place to distribute their talents and creativities. The design of the art center is intended as a place that can facilitate the activities of artists and the art communities in Surabaya to East Java. This design uses a flexible approach to space, viewed from many communities and artists of the existing art with different flow in Surabaya. Space facilities that will be designed include art gallery, sculpture workshop, painting workshop, cafe, office, and gift shop.